THE ESSENCE AND PECULIARITIES OF ILLEGAL MIGRATION IN UKRAINE AS AN OBJECT OF ADMINISTRATIVE AND LEGAL INFLUENCE (Bulletin of criminological association of Ukraine, 2024)
The article defines the essence of illegal migration, which consists inillegally crossing the border or staying on the territory of the state without the corresponding legal status, violating the relevant legislation. It is a complex phenomenon that has numerous social, economic and political aspects. The peculiarities of illegal migration in Ukraine, including characteristic routes, typical manifestations and motivational factors, were studied. It is noted that Ukraine, as a transit country on the way of migrants to the countries of the European Union, faces significant challenges related to the control of illegal migration flows. The key factors contributing to illegal migration in Ukraine, such as economic difficulties, social conflicts, political instability and insufficient effectiveness of the migration policy, have been identified. Based on the analysis, possible strategies and instruments of administrative and legal influence on illegal migration in Ukraine are considered. Among them are legislative measures, strengthening of control over the state border, implementation of administrative sanctions, etc. Based on the analysis of illegal migration in Ukraine, it is indicated that there are important aspects that require attention when developing strategies to combat this phenomenon. For example, it is necessary to consider the impact of migration processes on the labor market, national security and social stability. In addition, it is important to emphasize the importance of international cooperation in combating illegal migration, since this phenomenon has a cross-border nature and requires joint efforts of countries for effective control. Attention should also be paid to the importance of supporting legal migration flows by creating attractive conditions for legal migration, which can contribute to the reduction of illegal migration routes. Finally, it is important to consider the rights and dignity of illegal migrants in the process of developing and implementing migration control policies.
Keywords: illegal migration; essence and features; object of administrative and legal influence; administrative and legal regulation; public administration; administrative legislation